Women Empowerment through Self Help Groups: A Case Study in the North Tamil Nadu - Vinayagamoorthy, A.; Pithadia, Vijay (Indian Journal of Marketing, 2007)
Poverty and unemployment are the major problems of under developed countries, to which India is no exception. In India, at the end of ninth five-year plan, 26.1% of the population was living below the poverty line. In the rural area, 27.1% of the population was living under poverty. The overall unemployment rate is estimated to be 7.32%. The female unemployment rate is 8.5%. The rate of growth of women unemployment in the rural area is 9.8%. This is because of the low growth rate of new and productive employment. At the end of the IX plan, the rate of growth implemented by various schemes was to reduce poverty and to promote the gainful employment. But the more attractive scheme with less effort (finance) is "Self Help Group". It is a tool to remove poverty and improve the rural development (Sabyasachi Das. 2003).